THE EFFECT OF DIGITAL MARKETING AND PRODUCT QUALITY ON THE SALE OF FISHERMAN'S CATCH OF COASTAL COMMUNITIES OF SOUTHEAST SULAWESI - Ahsan Qasas; Eka Dharma Putra; Mirad Mirad; Ade Arya Pramana; La Ode Keeke (Jurnal Scientia, 2023)
This study aims to determine (1) the effect of digital marketing on the sale of fishermen's catch, (2) the effect of product quality on the sale of product quality on the sale of fishermen's catch, (3) the effect of digital marketing and product quality on the sale of fishermen's catch. The number of samples in this study were 100 respondents. The results of the study show that digital marketing has a very good effect on the sale of fishermen's catches of 0.398. Product quality is proven to have a positive effect of 0.678 on sales,